UTILIZATION OF AFRICAN LEAVES (VERNONIA AMYGDALINA) TO LOWER BLOOD PRESSURE IN PATIENTS WITH HYPERTENSION: A SYSTEMATIC REVIEW - Putri, Adira Aulia; Mukaromah, Irdat; Pratiwi, Novi Dwi; Alivian, Galih Noor (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Introduction: Hypertension is a non-communicable disease caused by genetics, stress, and lack of physical activity. So far, no effective drugs have been found to cure high blood pressure. Vernonia amygdalina contains substances that can lower blood pressure, namely flavonoids and potassium. Purpose: The systematic review aims to assess the potential of vernonia amygdalina in lowering blood pressure in hypertensive people. Methods: Articles are obtained from electronic databases such as PubMed, ScienceDirect, and Google Scholar published from 2011 to 2021. Keywords used: (